Obshchestvennoe mnenie . Obshchestvennoe mnenie . Public Opinion . Общественное мнение - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the power crisis; President Boris Yeltsin's address to the citizens of Russia; dissolution of the Supreme Soviet of the Russian Federation. Featured in the program: Levada, IUrii Aleksandrovich (Sociologist); Nuikin, Andrei Aleksandrovich (Writer); Antonov, Anatolii Nikolaevich (Sociologist); Aivazian, Mikhail Sergeevich (Political Scientist) Contributors: Maksimova, Tamara (Anchor) Обсуждение кризиса власти; обращение Президента Бориса Ельцина к гражданам России; роспуск Верховного Совета Российской Федерации. В программе участвуют: Левада, Юрий Александрович (Социолог); Нуйкин, Андрей Александрович (Писатель); Антонов, Анатолий Николаевич (Социолог); Айвазян, Михаил Сергеевич (Политолог) Создатели: Максимова, Тамара (Ведущий/Ведущая)